Prevalência e caracterização do processo estiloide alongado em uma população do sul do Brasil - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
Objective: the aim of the present study was to investigate the prevalence of the elongated styloid process by panoramic radiography and characterize them by sex, age, side of elongation and morphologic. Materials and Methods: the approach was a retrospective, descriptive study. It was analyzed digital medical records and panoramic radiography from 240 subjects over 18 years old. All data were registered with the Odontology Clinic between 2021 and 2022. The exams were performed using the panoramic radiography (model Eagle, DABI, Atlante) and the images were analyzed by the software from the equipment. It was adopted the morphological classification proposed by Langlais. Finally, it was performed the statistical analyzes. Results: the prevalence of the elongated styloid process was 20,8%, mostly in women, between 18 to 39 years old, bilateral and morphological classification type I. Conclusion: the present study showed that elongated styloid process was a common finding, and it should be considered in clinical cases of pain or discomfort orofacial. Therefore, it must to disseminate the characteristics and symptoms from elongated styloid process, mostly for health professionals.
Keywords: Prevalência; Alongamento ósseo; Radiografia panorâmica; Fonoaudiologia; Odontologia; Prevalence; Bone Lengthening; Radiography Panoramic; Speech, Language and Hearing Sciences.; Dentistry; CNPQ::CIENCIAS DA SAUDE